Etrolizumab versus adalimumab or placebo as induction therapy for moderately to severely active ulcerative colitis (HIBISCUS): two phase 3 randomised, controlled trials. (January 2022) - Rubin, David T; Dotan, Iris; DuVall, Aaron; Bouhnik, Yoram; Radford-Smith, Graham; Higgins, Peter D R; Mishkin, Daniel S; Arrisi, Pablo; Scalori, Astrid; Oh, Young S; Tole, Swati; Chai, Akiko; et al.
Summary: Background: Etrolizumab is a gut-targeted anti-β7 integrin monoclonal antibody. In an earlier phase 2 induction study, etrolizumab significantly improved clinical remission relative to placebo in patients with moderately to severely active ulcerative colitis. The HIBISCUS studies aimed to compare the efficacy and safety of etrolizumab to adalimumab and placebo for induction of remission in patients with moderately to severely active ulcerative colitis. Methods: HIBISCUS I and HIBISCUS II were identically designed, multicentre, phase 3, randomised, double-blind, placebo-controlled and active-controlled studies of etrolizumab, adalimumab, and placebo in adult (18–80 years) patients with moderately to severely active ulcerative colitis (Mayo Clinic total score [MCS] of 6–12 with an endoscopic subscore of ≥2, a rectal bleeding subscore of ≥1, and a stool frequency subscore of ≥1) who were naive to tumour necrosis factor inhibitors. All patients had an established diagnosis of ulcerative colitis for at least 3 months, corroborated by both clinical and endoscopic evidence, and evidence of disease extending at least 20 cm from the anal verge. In both studies, patients were randomly assigned (2:2:1) to receive subcutaneous etrolizumab 105 mg once every 4 weeks; subcutaneous adalimumab 160 mg on day 1, 80 mg at week 2, and 40 mg at weeks 4, 6, and 8; or placebo. Randomisation was stratified by baseline concomitant treatment with corticosteroids, concomitant treatment with immunosuppressants, and baseline disease activity. All patients and study site personnel were masked to treatment assignment. The primary endpoint was induction of remission at week 10 (defined as MCS of 2 or lower, with individual subscores of 1 or lower, and rectal bleeding subscore of 0) with etrolizumab compared with placebo. Pooled analyses of both studies comparing etrolizumab and adalimumab were examined for several clinical and endoscopic endpoints. Efficacy was analysed using a modified intent-to-treat population, defined as all randomly assigned patients who received at least one dose of study drug. These trials are registered with ClinicalTrials.gov, NCT02163759 (HIBISCUS I), NCT02171429 (HIBISCUS II). Findings: Between Nov 4, 2014, and May 25, 2020, each study screened 652 patients (HIBISCUS I) and 613 patients (HIBISCUS II). Each study enrolled and randomly assigned 358 patients (HIBISCUS I etrolizumab n=144, adalimumab n=142, placebo n=72; HIBISCUS II etrolizumab n=143; adalimumab n=143; placebo n=72). In HIBISCUS I, 28 (19·4%) of 144 patients in the etrolizumab group and five (6·9%) of 72 patients in the placebo group were in remission at week 10, with an adjusted treatment difference of 12·3% (95% CI 1·6 to 20·6; p=0·017) in favour of etrolizumab. In HIBISCUS II, 26 (18·2%) of 143 patients in the etrolizumab group and eight (11·1%) of 72 patients in the placebo group were in remission at week 10, with an adjusted treatment difference of 7·2% (95% CI –3·8 to 16·1; p=0·17). In the pooled analysis, etrolizumab was not superior to adalimumab for induction of remission, endoscopic improvement, clinical response, histological remission, or endoscopic remission; however, similar numerical results were observed in both groups. In HIBISCUS I, 50 (35%) of 144 patients in the etrolizumab group reported any adverse event, compared with 61 (43%) of 142 in the adalimumab group and 26 (36%) of 72 in the placebo group. In HIBISCUS II, 63 (44%) of 143 patients in the etrolizumab group reported any adverse event, as did 62 (43%) of 143 in the adalimumab group and 33 (46%) in the placebo group. The most common adverse event in all groups was ulcerative colitis flare. The incidence of serious adverse events in the pooled patient population was similar for etrolizumab (15 [5%] of 287) and placebo (seven [5%] of 144) and lower for adalimumab (six [2%] of 285). Two patients in the etrolizumab group died; neither death was deemed to be treatment related. Interpretation: Etrolizumab was superior to placebo for induction of remission in HIBISCUS I, but not in HIBISCUS II. Etrolizumab was well tolerated in both studies. Funding: F Hoffmann-La Roche.